2014
DOI: 10.4236/wja.2014.42020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Age on CD4 Response to Combination Antiretroviral Therapy: A Study in Tehran, Iran

Abstract: Background: This study was undertaken to address the controversy regarding immunologic response to combination antiretroviral therapy (cART) among older patients. Methods: In a crosssectional study all patients attending the HIV Clinic at Imam Khomeini Hospital (Tehran) from 2010 to 2011 were evaluated. Immunologic response was investigated using consecutive CD4+ T-cell counts in a one-year interval and outcomes were analyzed for older (>=50 yrs) and younger (<50 yrs) patients using SPSS version 16.0. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
(15 reference statements)
3
4
1
Order By: Relevance
“…The younger people below the age of 40 have higher chances of immune recovery than the older ones. This finding is supported by some previous studies who concluded lower mean CD4 increases for older patients than younger patients [ 20 , 26 ]. Alioum and others further argued that this could be caused by the fact that older subjects may have a reduced capacity to generate CD4 cells in response to the viral killing [ 10 ].…”
Section: Discussionsupporting
confidence: 90%
“…The younger people below the age of 40 have higher chances of immune recovery than the older ones. This finding is supported by some previous studies who concluded lower mean CD4 increases for older patients than younger patients [ 20 , 26 ]. Alioum and others further argued that this could be caused by the fact that older subjects may have a reduced capacity to generate CD4 cells in response to the viral killing [ 10 ].…”
Section: Discussionsupporting
confidence: 90%
“…The results are corroborated by the findings from a study that was carried out in Tehran, Iran, which showed that mean CD4 cell count increments after initiation of antiretroviral therapy are lower on older patients (> = 50 years) [12]. Prior to the study by Hasib et al [12], a study from Greece showed higher magnitudes of absolute CD4 cell count among patients 50 years and older [13]. The results reveal that, although HIV/AIDS patients generally take longer to reach a normal CD4 cell count compared to the time taken to reach an undetectable viral load, patients below the age of 45 years have reduced risks of mortality once the CD4 cell count is normal.…”
Section: Discussionsupporting
confidence: 64%
“…Patients below the age of 45 years had lower rates of viral load suppression to undetectable levels but they had faster rates of immune recovery compared to the older patients in the cohort (above 45 years of age). The results are corroborated by the findings from a study that was carried out in Tehran, Iran, which showed that mean CD4 cell count increments after initiation of antiretroviral therapy are lower on older patients (> = 50 years) [12]. Prior to the study by Hasib et al [12], a study from Greece showed higher magnitudes of absolute CD4 cell count among patients 50 years and older [13].…”
Section: Discussionmentioning
confidence: 56%
“…Generally younger patients experienced higher rates of immune recovery than immune deterioration compared to patients who are over 45 y and this concurs with findings from previous studies [14]. This is in agreement with previous study carried out in Tehran, India that showed that mean CD4 cell count increments after initiation of combination therapy are lower on older patients [15].…”
Section: Assessment Of the Fitted Modelssupporting
confidence: 92%
“…Lee et al [11] investigated the most vulnerable racial minority races (African Americans) in the United States and the Caucasians in order to predict the trends of the HIV/AIDS ISSN 0970-938X www.biomedres.info Biomedical Research 2018; 29 (15): 3090-3098 epidemic using a Markov chain analysis. They predicted from these races, the number of people living with HIV, and mortality count due to HIV/AIDS.…”
Section: Introductionmentioning
confidence: 99%